Pre-harvest methyl jasmonate spray maintains postharvest quality of Kinnow mandarin (Citrus reticulata) fruits - DHAMI, K S; ASREY, RAM; SHARMA, R R; SAGAR, V R; DASH, SUKANTA; DUBEY, A K (The Indian Journal of Agricultural Sciences, 2021)
The study was carried out at the experimental orchard of Indian Agricultural Research Institute, New Delhi (2019-20) to evaluate the pre-harvest effect of methyl jasmonate (MeJA) on postharvest quality of Kinnow mandarin (Citrus reticulata Blanco) under low temperature storage. Fruits were sprayed on tree with four concentrations of MeJA (0.1 mM, 0.3 mM, 0.5 mM, 0.7 mM) and control (distilled water) at 40 days and 20 days before commercial harvesting. The harvested fruits were stored consecutively at 2oC for 20 days followed by at 6oC for 20 days with 85-95% relative humidity. All the treatments showed significant results than control, but fruits treated with 0.5 mM MeJA retained higher moisture content (least water loss) and firmness with increase in TSS, acidity, total phenols, ascorbic acid, antioxidant and peroxidase enzyme activity during the storage period of 40 days. Therefore, pre-harvest spray @ 0.5mM MeJA could be an effective alternative to synthetic chemical use in maintaining the quality of Kinnow mandarin fruits during low temperature storage.